Comparative analysis of data synchronization policies for ensuring survivability of information systems on mobile platform - Рубан, І. В.; Ткачов, В. М. (My University, 2025)
The paper considers a class of information systems on a mobile platform with intermittent connectivity and dynamic exchange delays. Under such conditions, survivability is considered as the ability of an information system to maintain a correct and recoverable state of data in replicas, despite connection breaks during data retrieval and data update conflicts.